Gestão do desempenho individual na administração pública estadual : proposta de modelo à Secretaria de Estado da Administração de Sergipe – SEAD/SE - Santos, Rafael Lima (2023)
The debate on performance in the public sector must be understood in a broader context of changes in the role of the State and the transition from a bureaucratic model to a managerial model of public administration. In the context of managerial thinking, the organization's degree of efficiency is related to individual performance, encouraging the use of techniques and instruments that can contribute to unsatisfactory performance. The transposition of the practice originated in the private sector to the public sector, however, faces challenges. Cultural traits such as patrimonialism and clientelism, fear of personal emotions and political repercussions and aversion to potential conflicts remain in Brazilian public management. The work in the sector is of a collective nature, inter and intra organizational cooperation, making it difficult to individualize deliveries. Faced with this scenario and also taking into account that an effective performance management system must consider particular organizational characteristics, this research sought to develop a proposal for an individual performance management model applicable to the reality of the Secretaria de Estadop da Administração de Sergipe (SEAD/SE). For that, a case study was carried out in the organization in question. Data collection was done through documentary research, as well as through the application of forms. Data were treated through descriptive statistics and content analysis. The results supported a proposal for an individual performance management model for SEAD/SE, with the aim of introducing innovative practices for people management in the institution, for the benefit of employees, the organization and the state public administration as a whole.